The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4213/mzm10157
|View full text |Cite
|
Sign up to set email alerts
|

Типичное Перемешивание Имеет Ранг $1$

Abstract: Полная метрика на множестве перемешивающих преобразованиях, задаю-щая поводок-топологию, введена С. В. Тихоновым в 2007 г. Тихонов ставит во-прос: каким должно быть перемешивающее преобразование , чтобы его класс сопряженности был плотен в пространстве перемешиваний, снабженном пово-док-топологией? В статье будет показано, что это верно для любого перемеши-вающего . В качестве следствия из этого факта мы получим, что типичное перемешивание имеет ранг 1.Библиография: 13 названий.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…The set of rank-one transformations is a G δ set (use the proof from [2]). We have found that the class of mixing rank one transfomations is dense in Mix ∞ .…”
Section: Density Of the Conjugacy Classes Of The Sidon Automorphismsmentioning
confidence: 99%
See 3 more Smart Citations
“…The set of rank-one transformations is a G δ set (use the proof from [2]). We have found that the class of mixing rank one transfomations is dense in Mix ∞ .…”
Section: Density Of the Conjugacy Classes Of The Sidon Automorphismsmentioning
confidence: 99%
“…3 Типичность ранга один в Mix ∞ Альперн и Тихонов [1], [7] ввели полную метрику на пространстве перемешивающих действий. Баштанов [2] доказал, что класс действий ранга один типичен в пространстве Mix обратимых перемешивающих преобразований с инвариантной вероятностной мерой. Мы установим аналогичную теорему для пространства Mix ∞ = {T : T n → 0} преобразований T с сигма-конечной инвариантной мерой.…”
Section: Density Of the Conjugacy Classes Of The Sidon Automorphismsunclassified
See 2 more Smart Citations